2014
DOI: 10.1038/ncomms5107
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of hydrogen sulphide metabolism impairs oviductal transport of embryos

Abstract: Embryo retention in the fallopian tube is thought to lead to ectopic pregnancy, which is a significant cause of morbidity. Hydrogen sulphide (H 2 S) is a gaseotransmitter produced mainly by cystathionine-g-lyase and cystathionine-b-synthase. Here we show that cystathionine-g-lyase and cystathionine -b-synthase are ubiquitously distributed in human fallopian tube epithelium and that H 2 S signalling relaxes the spontaneous contraction of the human oviduct. Furthermore, an aberration in H 2 S signalling, either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…H 2 S is abundant in the Fallopian tube epithelial cells and synthesized intrinsically through the cell cytoplasm. This signaling pathway is upregulated during pregnancy and is mainly responsible for spontaneous oviduct muscle contraction, which provides a positive factor to the embryo movement toward the uterus (Ning et al 2014). Nitric oxide has been identified in the Fallopian tube; it mediates tubal muscle contraction, with possible roles in the regulation of sperm motility (Ekerhovd et al 1997, Kobayashi et al 2016.…”
Section: Gas In the Oviductmentioning
confidence: 99%
“…H 2 S is abundant in the Fallopian tube epithelial cells and synthesized intrinsically through the cell cytoplasm. This signaling pathway is upregulated during pregnancy and is mainly responsible for spontaneous oviduct muscle contraction, which provides a positive factor to the embryo movement toward the uterus (Ning et al 2014). Nitric oxide has been identified in the Fallopian tube; it mediates tubal muscle contraction, with possible roles in the regulation of sperm motility (Ekerhovd et al 1997, Kobayashi et al 2016.…”
Section: Gas In the Oviductmentioning
confidence: 99%
“…Thus, the effect of other products of CSE and CBS on PGDH expression cannot be excluded. Interestingly, Ning et al 33 recently showed that CBS and CSE have a differential role in oviductal embryo transport, although the hydrogen sulfide donor shows the regulatory effect on oviduct contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Roles for H 2 S in female reproductive biology have only recently come to light. For example, both CBS and CSE are expressed in human intrauterine tissues and placenta (Patel, Vatish, Heptinstall, Wang, & Carson, 2009;You et al, 2011) as well as in epithelial cells of the fallopian tubes (Ning et al, 2014). The first direct evidence suggesting a role for H 2 S in reproductive biology was in preeclampsia, a hypertensive condition that affects around 4% of all pregnancies.…”
Section: Effect Of Gyy4137 In the Reproductive Systemmentioning
confidence: 99%
“…Interestingly, egg retention within the fallopian tube is associated with ectopic pregnancy and deregulation of fallopian tube contractility may play a part in this process. Indeed, disruption of H 2 S signaling has recently been reported to promote embryo retention and cause developmental delay in the mouse whilst pharmacological treatment with either GYY4137 or NaHS reversed these effects and restored the status quo (Ning et al, 2014).…”
Section: Effect Of Gyy4137 In the Reproductive Systemmentioning
confidence: 99%